Tracing the development of nationalist attitudes in the EU. (June 2021) - Clark, Nicholas; Rohrschneider, Robert
We discuss the relevance of national attachments for European integration, reviewing the existing literature and drawing connections across the articles in this issue. We also consider that the ageing European population might be a possible explanation for why nationalism is increasingly shaping EU support especially outside the ideological extremes. Taken together with the other contributions in this issue, it is quite possible that national identity will increasingly shape the views of individuals with ideologically moderate views who in the past have supported European integration.